2009
DOI: 10.1016/j.neuroscience.2009.02.049
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol-induced delta-opioid receptor modulation of glutamate synaptic transmission and conditioned place preference in central amygdala

Abstract: Alcoholism involves compulsive behaviors of alcohol drinking, which is thought to be related at least initially to the rewarding effect of alcohol. It has been shown that mu-opioid receptors play an essential role in drug reward and dependence for many drugs of abuse including alcohol, but the function of delta-opioid receptors (DOR) in drug reward remains largely unknown at present. Previous animal studies using systemic approaches with DOR antagonists or DOR knockout animals have yielded inconsistent results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 63 publications
(104 reference statements)
2
34
0
Order By: Relevance
“…In particular, we would expect chronic ethanol to up-regulate the number or function of DOR1s in circuits or brain regions that control anxiety. This hypothesis is supported by recent findings that chronic ethanol exposure recruited functional DORs in the central nucleus of the amygdala (Bie et al, 2009). Intriguingly, a recent study showed that DORs are involved in the function of benzodiazepines (Primeaux et al, 2006).…”
Section: Discussionsupporting
confidence: 73%
“…In particular, we would expect chronic ethanol to up-regulate the number or function of DOR1s in circuits or brain regions that control anxiety. This hypothesis is supported by recent findings that chronic ethanol exposure recruited functional DORs in the central nucleus of the amygdala (Bie et al, 2009). Intriguingly, a recent study showed that DORs are involved in the function of benzodiazepines (Primeaux et al, 2006).…”
Section: Discussionsupporting
confidence: 73%
“…Hence, knockout mice exhibit impaired learning to both appetitive and aversive stimuli, suggesting it is necessary contextual learning. Moreover, there is evidence that DOPr may also be important in memory retrieval, because the expression of place preference and opioid reinstatement was prevented by acute DOPr antagonist administration immediately prior to post-conditioning day testing, after conditioning to morphine (Bie et al, 2012) or ethanol (Bie et al, 2009a). Nevertheless, DOPr membrane translocation, as measured by immunogold electron microscopy techniques, was evident 48 hours after withdrawal from a 2-week binge cocaine protocol (Ambrose-Lanci et al, 2008).…”
Section: Confoundsmentioning
confidence: 99%
“…DORs are primarily expressed in mechanical pain sensing neurons (Scherrer et al, 2009; van Rijn et al, 2012) and play a crucial role in touch and mechanical sensation (Bardoni et al, 2014; Scherrer et al, 2009), making it a promising target to treat withdrawal hyperalgesia that is generally associated with increased tactile sensation. Moreover, alcohol exposure can elevate functional DOR expression in different areas of the central nervous system (Bie et al, 2009; Margolis et al, 2008; van Rijn et al, 2012). We, therefore, propose that DORs could be a novel target for alcohol withdrawal-induced mechanical allodynia (AWiMA) therapy, particularly considering that DOR agonists also reduce alcohol consumption (van Rijn and Whistler, 2009) and attenuate anxiety-like behaviors in alcohol-withdrawn mice (van Rijn et al, 2010).…”
Section: Introductionmentioning
confidence: 99%